The “Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies” (SPRINTT) randomized controlled trial: design and methods - Landi, Francesco; Cesari, Matteo; Calvani, Riccardo; Cherubini, Antonio; Di Bari, Mauro; Bejuit, Raphael; Mshid, Jerome; Andrieu, Sandrine; Sinclair, Alan J.; Sieber, Cornel C.; Vellas, Bruno; Topinkova, Eva; et al. (Aging clinical and experimental research, 2017)
The sustainability of health and social care systems is threatened by a growing population of older persons with heterogeneous needs related to multimorbidity, frailty, and increased risk of functional impairment. Since disability is difficult to reverse in old age and is extremely burdensome for individuals and society, novel strategies should be devised to preserve adequate levels of function and independence in late life. The development of mobility disability, an early event in the disablement process, precedes and predicts more severe forms of inability. Its prevention is, therefore, critical to impede the transition to overt disability. For this reason, the Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies (SPRINTT) project is conducting a randomized controlled trial (RCT) to test a multicomponent intervention (MCI) specifically designed to prevent mobility disability in high-risk older persons. SPRINTT is a phase III, multicenter RCT aimed at comparing the efficacy of a MCI, based on long-term structured physical activity, nutritional counseling/dietary intervention, and an information and communication technology intervention, versus a healthy aging lifestyle education program designed to prevent mobility disability in 1500 older persons with physical frailty and sarcopenia who will be followed for up to 36 months. The primary outcome of the SPRINTT trial is mobility disability, operationalized as the inability to walk for 400 m within 15 min, without sitting, help of another person, or the use of a walker. Secondary outcomes include changes in muscle mass and strength, persistent mobility disability, falls and injurious falls, disability in activities of daily living, nutritional status, cognition, mood, the use of healthcare resources, cost-effectiveness analysis, quality of life, and mortality rate. SPRINTT results are expected to promote significant advancements in the management of frail older persons at high risk of disability from both clinical and regulatory perspectives. The findings are also projected to pave the way for major investments in the field of disability prevention in old age.